Respuesta :
d/dx(xcosx)+d/dx(2tanx)
= (1*cosx + x*(-sinx) + 2sec^2(x)
= cosx - xsinx + 2sec^2(x)
= (1*cosx + x*(-sinx) + 2sec^2(x)
= cosx - xsinx + 2sec^2(x)
Answer:
[tex]\frac{dy}{dx}=\cos x-x\sin x+2\sec^2x[/tex]
Step-by-step explanation:
Given : Function [tex]f(x)=x\cos x+2\tan x[/tex]
To find : How do I differentiate the function ?
Solution :
Let [tex]y=x\cos x+2\tan x[/tex]
Differentiate w.r.t x,
[tex]\frac{dy}{dx}=\frac{d(x\cos x)}{dx}+\frac{d(2\tan x)}{dx}[/tex]
Apply product rule, [tex]\frac{d}{dx}(u\cdot v)=u'v+v'u[/tex]
[tex]\frac{dy}{dx}=\frac{d}{dx}(\cos x)x+\cos x\frac{d}{dx}(x)+2\sec^2x[/tex]
[tex]\frac{dy}{dx}=-x\sin x+\cos x+2\sec^2x[/tex]
Therefore, [tex]\frac{dy}{dx}=\cos x-x\sin x+2\sec^2x[/tex]